2018
DOI: 10.1038/s41467-018-05007-9
|View full text |Cite
|
Sign up to set email alerts
|

Dedicated surveillance mechanism controls G-quadruplex forming non-coding RNAs in human mitochondria

Abstract: The GC skew in vertebrate mitochondrial genomes results in synthesis of RNAs that are prone to form G-quadruplexes (G4s). Such RNAs, although mostly non-coding, are transcribed at high rates and are degraded by an unknown mechanism. Here we describe a dedicated mechanism of degradation of G4-containing RNAs, which is based on cooperation between mitochondrial degradosome and quasi-RNA recognition motif (qRRM) protein GRSF1. This cooperation prevents accumulation of G4-containing transcripts in human mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(115 citation statements)
references
References 70 publications
5
110
0
Order By: Relevance
“…Indeed, the RNA-binding protein GRSF1 has been shown to bind and promote G4 melting within mitochondrial-transcribed RNAs that, in turn, facilitates their degradasome-mediated decay 23 . In both K562 and HepG2 cells, we observe similar enrichment for GRSF1 binding over 5' and 3' UTR pG4 sequences, leading us to speculate that a similar mechanism may exist to melt pG4 sequences, and promote degradation of their parent RNA transcripts in human cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the RNA-binding protein GRSF1 has been shown to bind and promote G4 melting within mitochondrial-transcribed RNAs that, in turn, facilitates their degradasome-mediated decay 23 . In both K562 and HepG2 cells, we observe similar enrichment for GRSF1 binding over 5' and 3' UTR pG4 sequences, leading us to speculate that a similar mechanism may exist to melt pG4 sequences, and promote degradation of their parent RNA transcripts in human cells.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis revealed enrichment for proteins that have been implicated in RNA G4 binding (GRSF1, FUS), and those that, to our knowledge, have not previously been associated with RNA G4 structures (PRPF4, GTF2F1, and CSTF2T). GRSF1 is a cytoplasmic protein involved in viral mRNA translation, and has recently been shown to play a role in the degradation of G4-containing RNAs in mitochondria 22,23 . Other proteins with significant enrichment for pG4 Table 4).…”
Section: Rna-protein Binding Sites Are Enriched Over Utr Pg4 Regionsmentioning
confidence: 99%
“…While the complex of leucine rich pentatricopeptide repeat containing and SRA stem-loop interacting RNA binding proteins (LRPPRC-SLIRP complex) was suggested to suppress the degradosome-mediated decay of mitochondrial protein-coding RNAs [102]. G-rich RNA sequence binding factor 1 (GRSF1) was recently found to enhance the degradosome activity towards mtRNAs containing a G-quadruplex (G4), which are mostly non-coding mtRNAs [106].…”
Section: Degradation Of Mtrnasmentioning
confidence: 99%
“…It was postulated that GRSF1 participates in the initial stages of polycistronic mtRNA precursor processing [116] and in the translation of some mt-mRNAs [115]. Recent findings, however, reported that GRSF1 takes part in the RNA surveillance pathway, showing that GRSF1 cooperates with the mitochondrial degradosome to regulate mtRNAs that contain G4s [106]. Vertebrates' mitochondrial genomes have exceptional GC skews, i.e., high guanine content on one strand.…”
Section: Mitochondrial Rna-binding Proteins (Mtrbps)mentioning
confidence: 99%
See 1 more Smart Citation